2017
DOI: 10.1007/s11605-017-3355-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Colectomy Is Independently Associated with Decreased Long-Term Overall Survival in Colon Cancer Patients

Abstract: Emergent resection for colon cancer is independently associated with poor short-term outcomes and decreased 5-year OS compared to elective resection. With 30% of cases in this study emergent, these findings underlie the importance of adherence to colon cancer screening guidelines to limit the need for emergent resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 39 publications
5
48
0
Order By: Relevance
“…Our study confirmed similar findings, showing that 28 patients (41%) with CCC presented with clinical stage III or IV. Other studies have also reported advanced stages in patients undergoing emergency surgical treatment 6,7,22.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our study confirmed similar findings, showing that 28 patients (41%) with CCC presented with clinical stage III or IV. Other studies have also reported advanced stages in patients undergoing emergency surgical treatment 6,7,22.…”
Section: Discussionmentioning
confidence: 87%
“…Despite screening methods, up to 43% of patients will develop some form of complication including obstruction, perforation or hemorrhage 4-7. Emergency surgery has a direct impact on results.…”
Section: Introductionmentioning
confidence: 99%
“…An emergency colectomy for perforation or obstruction is a stronger prognostic factor than a pathological finding of perforation [28].…”
Section: Clinical Presentationmentioning
confidence: 97%
“…A previous meta-analysis including 1062 patients reported 87% of unresectable stage IV patients with tumor-related complication required surgical intervention, thereby underlining the importance of PTR to such patients [ 23 ]. However, emergent surgery has been proved to be associated with the great risk and poor oncological outcome [ 24 26 ]. Besides, a symptomatic obstruction that requires surgery occurs in approximately 20% of patients before death [ 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%